The credibility of intermediate hyperglycemia (IH) at one hour of OGTT in 30 β-thalassemia patients (β-thal) with persistent low iron overload - Campisi, Saveria; De Sanctis, Vincenzo; Soliman, Ashraf; Daar, Shahina; Kattamis, Christos (Acta Biomedica Atenei Parmensis, 2024)
Background: Intermediate hyperglycemia (IH) at 1-hour during oral glucose tolerance test (OGTT) has received attention as a useful early biomarker of dysglycemia. Objective: The main objective of this  study was to gain further insight into IH in 30 β-thalassemia (β-thal) patients with a spectrum of genotypes  and persistent low iron load (serum ferritin; SF: